2003
DOI: 10.1097/00004872-200312000-00027
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of nitric oxide synthases and nitrotyrosine in the kidney of spontaneously hypertensive rats

Abstract: The expression of nNOS is higher in the renal medulla of the SHR, and the distribution of eNOS, iNOS and nitrotyrosine is similar in SHR and WKY rats. It is proposed that the higher expression of the neuronal isoform in the medullary tubular cells is a protective mechanism aimed to improve renal function in spontaneous hypertension.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
15
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 28 publications
4
15
1
Order By: Relevance
“…( 25 ) that demonstrated increased NO production and upregulation of iNOS and eNOS protein expression in both prehypertensive (8-week-old) and hypertensive (12-week-old) SHR. On the other hand, at 20 − 25 weeks of age, the renal expression of nNOS is higher in SHR, but the distribution and the expression of both eNOS and iNOS are similar in SHR and WKY ( 29 ). With advanced age (63 weeks), untreated SHR show lower urinary NOx excretion and depressed renal NOS protein expression compared to untreated WKY, and these effects may be associated with the development of renal injury ( 30 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…( 25 ) that demonstrated increased NO production and upregulation of iNOS and eNOS protein expression in both prehypertensive (8-week-old) and hypertensive (12-week-old) SHR. On the other hand, at 20 − 25 weeks of age, the renal expression of nNOS is higher in SHR, but the distribution and the expression of both eNOS and iNOS are similar in SHR and WKY ( 29 ). With advanced age (63 weeks), untreated SHR show lower urinary NOx excretion and depressed renal NOS protein expression compared to untreated WKY, and these effects may be associated with the development of renal injury ( 30 ).…”
Section: Discussionmentioning
confidence: 99%
“…For example, a recent study demonstrated that a systemic increase in ADMA produces adverse cardiovascular effects in humans, including an increase in blood pressure, reduced heart rates and reduced cardiac output ( 29 ). Therefore, the decrease in ADMA levels by treatment with PPAR γ ligands may contribute to cardiovascular risk reduction.…”
Section: Fig 3 Effects Of Pioglitazone (Pio) On Protein Expression mentioning
confidence: 99%
“…It has long been recognized that activated polymorphonuclear cells (PMN) and monocytes can produce ROS and nitric oxide (NO) radicals [Hibbs et al, 1988]. Overproduced NO reacts rapidly with superoxide, yielding peroxynitrite, which causes renal injury via direct oxidant injury and protein tyrosine nitration [Ferna¤ ndez et al, 2003]. Whether NO plays a role in the increased ROS production in the renal venous blood and leukocyte in¢ltration of the renal tissue seen in our previous study is not known.…”
Section: Introductionmentioning
confidence: 78%
“…To test our hypothesis, intrarenal NO activity was tested by directly administering two diuretic stimuli, L-arginine or saline loading, and analyzing the urinary excretion of NO metabolites (nitrate and nitrite, NOx) and cGMP to measure the NO response; changes in the expression of the three NOS isoforms in the kidney were also evaluated. In order to investigate the correlation between enhanced in¢ltration of leukocytes, iNOS expression, and nitrosative stress, we measured levels of myeloperoxidase (MPO), iNOS, nitrotyrosine (indicator of peroxynitrite formation) [Ferna¤ ndez et al, 2003], and poly (ADP-ribose) polymerase (PARP, indicator of oxidative injury) [Chatterjee et al, 2000] in the kidneys of control and EG-treated rats.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, we tested for differential expression of cyclooxygenase 2 (COX-2), endothelial nitric oxide synthase (NOS), and neuronal NOS. Altered renal expression and function of these enzymes or decreased renal availability of their products is involved in the pathogenesis of experimental hypertension (9,23,39,41,44). COX-2 expression is developmentally regulated in rat kidneys (45), and renal neuronal NOS expression and function depend on renal innervation (16,41).…”
mentioning
confidence: 99%